The insula, a grey matter of tastes: a volumetric MRI study in dementia with Lewy bodies - Nathalie Philippi; Vincent Noblet; Malik Hamdaoui; David Soulier; Anne Botzung; Emmanuelle Ehrhard; Benjamin Cretin; Frédéric Blanc; AlphaLewyMA study group (Alzheimer’s Research & Therapy, 2020)
Abstract Background Despite the growing number of discoveries during the past decades about its functions, the insula remains a mysterious ‘island’. In addition to its involvement in basic functions such as gustation and interoception, the insular cortex is now considered a key region for integrated functions such as emotion/motivation processing, decision-making and self-consciousness. We hypothesized that this structure, standing at the crossroads of such functions, could ground personal tastes in general, beyond food preferences and aesthetic judgements. Given that dementia with Lewy bodies is characterized by a focal atrophy within the insular cortex from the early stages, this condition provides an opportunity to test such a hypothesis. Methods We developed a questionnaire to assess potential changes in personal tastes, submitted it to a cohort of 23 patients with early-stage dementia with Lewy bodies and compared their questionnaire results to those of 20 age-matched healthy controls. Furthermore, we performed a global and regional neuroimaging study to test for a potential correlation between the patients’ scores for changes in personal tastes and their insular cortex volumes. Results Our results indicate that the patients presented significant changes in personal tastes compared to the controls, in both food and non-food domains. Moreover, imaging analyses confirmed the involvement of the insular cortex atrophy in the changes in personal tastes using global analysis, and in both food and non-food domains using regional analysis. Conclusions These results bring new insights into the role of the insula as a ‘grey matter of tastes’, this structure supporting personal preferences in general, beyond the food domain. The insular cortex could be involved through its role in motivational processes by the representation of subjective awareness of bodily states during the phenomenological experience of stimulus appraisal. However, we also argue that it could support the abstract representations of personal tastes as self-concepts, acutely exemplifying embodied cognition. Finally, the questionnaire on changes in tastes could constitute an interesting tool to help early diagnosis of dementia with Lewy bodies and to assess insular dysfunction more generally.